Expression of Bax, p53, and p27/kip in patients with papillary thyroid carcinoma with or without cervical nodal metastasis - Karlidag, Turgut; Cobanoglu, Bengu; Keles, Erol; Alpay, Hayrettin Cengiz; Ozercan, Ibrahim; Kaygusuz, Irfan; Sakallioglu, Oner (W B Saunders Co-Elsevier Inc, 2007)
Objective: The purpose of this study is to investigate the expression of Bax, p53, and p27/kip1 in patients with papillary thyroid carcinoma (PTC) with or without cervical nodal metastasis and to determine the role of immunohistochemical markers for prediction of neck metastasis in these patients. Study design and setting: A retrospective review from 1998 to 2004 at the Department of Otorhinolaryngology, Firat University, Elazig, Turkey, was performed in the records of 28 patients with nonmetastasizing (n = 15) and metastasizing (n = 13) PTC. The immunoreactivity, for Bax, p53, and p27/kip1 protein in all tissue specimens were assessed. Results: p27 expression in the nonmetastasizing PTC was lower than normal thyroid tissue (P <.01) and higher than metastasizing PTC (P <.01). p53 immunoreactivity was present, faint(grade 1) staining in a small number of cells in 2 nonmetastasizing PTCs. In 13 nonmetastasizing PTCs and all of metastasizing PTCs, normal thyroid tissue had no immunoreactivity for p53. There was no statistically significant difference among all groups' immunoreactivity for p53. Expression of Bax in patients with PTC was more than normal thyroid tissue (P <.01). However, expression of Bax in the patients with nonmetastasizing and metastasizing PTC was similar. Conclusion: The immunohistochemical evaluation of p27 expression in patients with PTC may be useful to predict for metastasis risk of the PTC to regional lymph nodes. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: P27(Kip1) Expression; Cancer; Tumors; Disease; Impact; Prognosis; Survival